EDDIDAT: a graphical user interface for the analysis of energy‐dispersive diffraction data. Issue 4 (12th June 2020) - Apel, Daniel; Genzel, Martin; Meixner, Matthias; Boin, Mirko; Klaus, Manuela; Genzel, Christoph
Abstract : EDDIDAT is a program that provides a graphical user interface for the evaluation of energy‐dispersive X‐ray diffraction data with the focus on depth‐resolved residual stress analysis. Abstract : EDDIDAT is a MATLAB‐based graphical user interface for the convenient and versatile analysis of energy‐dispersive diffraction data obtained at laboratory and synchrotron sources. The main focus of EDDIDAT up to now has been on the analysis of residual stresses, but it can also be used to prepare measurement data for subsequent phase analysis or analysis of preferred orientation. The program provides access to the depth‐resolved analysis of residual stresses at different levels of approximation. Furthermore, the graphic representation of the results also serves for the consideration of microstructural and texture‐related properties. The included material database allows for the quick analysis of the most common materials and is easily extendable. The plots and results produced with EDDIDAT can be exported to graphics and text files. EDDIDAT is designed to analyze diffraction data from various energy‐dispersive X‐ray sources. Hence it is possible to add new sources and implement the device‐specific properties into EDDIDAT . The program is freely available to academic users.